Rekontruksi Saraf dengan Cangkok Saraf Sural di Lingkungan dengan Sumber Daya Terbatas: Laporan Kasus - Tuasikal, Rabinda Fitriana; Salim, Rakha Sulthan; Tualeka, Mo (PT Kalbe Farma Tbk., 2025)
Introduction: Nerve reconstruction is an essential procedure in the management of nerve damage. When end-to-end primary repair is not possible, an autologous nerve graft is the gold standard for management. The sural nerve is considered the most reliable harvest site. Compared to other reconstructive options, auto graft provides the best similar physiologic nerve environment for axonal regeneration. To achieve an efective neural regeneration, tension-free repair sites should be provided, as they hinder focal neural ischemia caused by disrupted microvascular fow. Case: A 52-year-old woman with a giant schwannoma of the ulnar nerve had a tumor excision surgery followed by sural nerve grafting in a low-resource setting where microsurgery equipment is unavailable. Maluku, with archipelago-type geography, poses signifcant challenges to healthcare professionals in performing guideline-based procedures. Conclusion: Considering the unavoidable risk of nerve damage and signifcant gap, tumor excision followed by nerve reconstruction using autograft was chosen in this case, resulting in a decent outcome.